Heat Shock Protein Gene Expression Analysis in Extensively Reared Indigenous Wad Goats - Tella, A. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
This study investigated the expression patterns of HSP90 and HSP70 genes, which encode heat shock proteins, using 45 genomic DNA samples isolated from West African Dwarf (WAD) goats in Nigeria. The polymorphism information content (PIC) of each marker was evaluated to determine its level of informativeness. DNA samples were collected from apparently healthy WAD goats in Osun, Oyo, and Kwara States under field heat-stress conditions, with ambient temperature and relative humidity recorded at the time of sampling. Polymerase chain reaction (PCR) amplification was performed using primers specific for each heat shock protein gene, and the PCR products were analyzed by polyacrylamide gel electrophoresis on an ABI 3730 DNA Sequencer. Allelic variation was assessed using Microsatellite Analyzer software to generate allele frequencies. The results revealed alleles A and C as the predominant alleles for markers SSR1 (HSP90) and SSR2 (HSP70), respectively. The effective number of alleles and expected heterozygosity were higher for SSR2 (He = 0.40) than for SSR1 (He = 0.36). PIC values ranged from 0.55 (HSP90) to 0.59 (HSP70), indicating that both markers were informative (PIC ≥ 0.50). This study provides the first molecular characterization of HSP90 and HSP70 gene polymorphisms in WAD goats under tropical heat-stress conditions, suggesting their potential as reliable genetic biomarkers for thermotolerance selection and future breeding programs aimed at improving heat resilience in tropical livestock. Keywords: Heat shock proteins; HSP90; HSP70; thermotolerance; West African Dwarf Goat